Study of Communicative and Collaborative Characteristics of Students using Inquiry Based Inquiry Based on Basic Acid Materials - Bella Listriani Putri; Maria Erna; Lenny Anwar (Universitas Riau, 2020)
Education today focuses on creating characters who are able to face future challenges. The first challenge in this global era is the need for every student to have process skills in 21st century learning known as 4C: (1) Communication Skills, (2) Collaboration skills, (3) Critical Thinking and (4) Creative. One of the characteristics desired in 21st century education is a communicative and collaborative character. The purpose of this study was to determine the improvement of the communicative and collaborative character of students after using guided inquiry-based e-LKPD on acid-base material. The form of this research was quasi-experimental research. The research sample consisted of 2 classes, namely the experimental class (XI MIA 1) and the control class (XI MIA 2). Based on the research, the results showed that the use of guided inquiry-based e-LKPD on acid-base material can improve the communicative and collaborative character of students through observation results with an average value in the experimental class, respectively, namely 89.25% and 85% with the high category compared the control class is 44.75% and 36.75% with the low category.